Pengaruh kebijakan hutang, good corporate governance dan cash holding terhadap nilai perusahaan manufaktur - Putri, Anisa Setya; Lisiantara, G.Anggana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study examines the effect of debt policy, good corporate governance and cash holing on firm value, where good corporate governance includes independent commissioner, managerial ownership, institutional ownership, audit committee and board size. The sample in this study used 198 data from 66 manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020 by using purposive sampling method. The analysis toold used are normality test, classical assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has deen done, the results of this study showed that debt policy, managerial ownership, institusional ownership and board size have a significant positive effect on firm value. While the independent commissioners have no significant negative effect on firm value, cash holding have a significant negative effect on firm value and audit committee have no significant effect on firm value.